The Effects of Epidermal Neural Crest Stem Cells on Local Inflammation Microenvironment in the Defected Sciatic Nerve of Rats - Li, Yue; Yao, Dongdong; Zhang, Jieyuan; Liu, Bin; Zhang, Lu; Feng, Hua; Li, Bingcang (Frontiers in Molecular Neuroscience, 2017)
Cell-based therapy is a promising strategy for the repair of PNI. EPI-NCSCs are thought to be important donor cells for repairing PNI in different animal models. Following PNI, inflammatory response is important to regulate the repair process. However, the effects of EPI-NCSCs on regulation of local inflammation microenviroment have not been investigated extensively. In the present study, these effects were studied by using 10 mm defected sciatic nerve, which was bridged with 15 mm artificial nerve composed of EPI-NCSCs, ECM and PLGA. Then the expression of pro- and anti-inflammatory cytokines, polarization of macrophages, regulation of fibroblasts and SCs were assessed by western blot, immunohistochemistry, immunofluorescence staining at 1, 3, 7 and 21 days after bridging. The structure and the function of the bridged nerve were determined by observation under light microscope and by examination of right LFRT, SFI, gastrocnemius wet weight and electrophysiology at 9 wks. After bridging with EPI-NCSCs, the expression of anti-inflammatory cytokines (IL-4 and IL-13) was increased, but decreased for pro-inflammatory cytokines (IL-6 and TNF-α) compared to the control bridging, which was consistent with increase of M2 macrophages and decrease of M1 macrophages at 7 days after transplantation. Likewise, myelin-formed SCs were significantly increased, but decreased for the activated fibroblasts in their number at 21 days. The recovery of structure and function of nerve bridged with EPI-NCSCs was significant superior to that with DMEM. These results indicated that EPI-NCSCs could be able to regulate and provide more suitable inflammation microenvironment for the repair of defected sciatic nerve.